If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 58 + -6 = 3x + 17 Combine like terms: 58 + -6 = 52 52 = 3x + 17 Reorder the terms: 52 = 17 + 3x Solving 52 = 17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 52 + -3x = 17 + 3x + -3x Combine like terms: 3x + -3x = 0 52 + -3x = 17 + 0 52 + -3x = 17 Add '-52' to each side of the equation. 52 + -52 + -3x = 17 + -52 Combine like terms: 52 + -52 = 0 0 + -3x = 17 + -52 -3x = 17 + -52 Combine like terms: 17 + -52 = -35 -3x = -35 Divide each side by '-3'. x = 11.66666667 Simplifying x = 11.66666667
| 3t-6=9-2t | | 233-7x=29x+21 | | 3.4x+8.7=1.7x+18.9 | | 10x+10=20x+20 | | x^5-x^3+x+1=0 | | 3x+x+2=2x-4 | | 31-9(y+5)=7 | | x^3-96x^2+576x=0 | | -17-9=8x+17 | | 7y-9=33 | | 4x24= | | 5(2x-1)+16=8x+1 | | 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 | | 1=14(2r+1) | | 14-6x=2x+66 | | 8x+29x-6= | | 1.4m-06(m-2)=2.4m | | 2x+40=12x-40 | | 5x-4=2x+6+x | | 37x=9x+4 | | 2(x-7)=10-4x | | 25x^2-15x-4=0 | | 12-6x=6x+34 | | 6x-10=46 | | 2+5+6rs= | | 2(y-6)-(y+2)=26 |